Mission based component plans - Keskin, M. Emre. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
One of the widely used methods of system reliability test plans is based on the idea of computing the component test plans that ensure prespecified reliability levels for those components. Another widely used approach suggests the determination of the system test plans which guarantee a certain reliability level for the system. Since the main concern is the reliability of the system, the latter approach can be thought as more advantageous over the former one. However, testing a system as a whole can be very costly, very difficult or even impossible, which makes the first approach more appropriate to use. The idea of combining the advantageous points of both approachs gave birth of another method called as system based component test plans. One can find many works in the literature that applies the system based com- ponent testing idea with respect to different system topologies. However, realibility definition employed in all of these studies assumes a prespecified amount of fixed time during which the object whose reliability is the concern, works without a failure. This reliability definition is invalid for systems designed to perform sequence of missions, which are possibly in random order and have possibly random durations. In this thesis, a new method which we call as mission based component test plans is proposed as a means for the determination of the optimum component test plans for series systems and serial connection of redundant subsystems.
Keywords: Reliability (Engineering)